New York Paper - Iron-Ores of the Potsdam Formation in the Valley of Virginia - Charles Catlett (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1900)
Some years ago the writer was struck by what might be called the remarkable vitality of the Virginia furnaces during the panic of 1893; and attention was called to the fact in the American Manufacturer of February 8,1895. From the second half of 1892, which was a period of maximum output, to the second half of 1893, when the full effects of the depression had been reached, the output of pig-iron had fallen off in Illinois 85; in New York, 66; in Ohio, 51; in Tennessee, 44; in Pennsylvania, 28; and in Virginia only 15 per cent. It seemed a reasonable inference that the State which had thus shown its marked ability to meet hard times could make and market its product with a larger margin of profit than any of the other States. This was true at that time, and to a certain extent the reasoning still holds good; but my mistake was in not fully realizing the marked effect of the Mesabi development, combined with reduced economies in transportation, and the consequent advantage to those furnaces which were so situated as to utilize these new commercial factors. The effect of these factors is seen in comparing the second half of 1894 with the second half of 1892. New York had dropped off 44, Alabama 23, Tennessee 21, Illinois 19, and Virginia 16 per cent., while Pennsylvania had increased 5 and Ohio 10 per cent. While there is no question of the great economy which has been made possible for certain interests which are peculiarly situated with reference to the ores of the Northwest, it is yet too early to say what furnaces not so fortunate will have to pay for their raw material. Already an increase of twenty cents per ton of ore has been announced, based upon increased cost of production.